(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Il caso - 3. L’iter processuale e gli argomenti. Materialità del fatto ed ermeneutica antropologica - 4. Un nuovo tassello nella cultural expertise: lo strumento della “audizione etnica” (escuta étnica) - 5. Il pluralismo giuridico dialogico e l’affidamento della sanzione alla comunità guaranì - 6. Il ruolo del giudice di fronte a pratiche culturali patriarcali - 7. Dal Brasile all’Europa: spunti di riflessione sui rapporti sessuali di infra-quattordicenni nel matrimonio rom e nella cultura italiana. Culturally motivated crimes in Brazil: the case of rape/non-rape among the Guaranì Indians (with remarks on Roma early marriages) * ABSTRACT: This article describes a culturally motivated crime that came to the attention of a Brazilian court: sexual intercourse with a girl under the age of fourteen in a Guaranì group, indios from the Mata Atlantica. The judge acquitted the accused taking into account the fact that in the Guaranì society a woman becomes an adult with menarche and that sexual initiation is widespread in this culture. The accused had violated the protocol of this initiation, for which he will be sanctioned according to the norms of Guaranì law. The Brazilian case allows for a series of observations on the debate on Roma early marriages that is taking place in Europe, and on the different treatment between sex acts in this context and sex acts between minors under fourteen years old and other teenagers in the majority cultures of Europe.